"A Personal Point of View": The Dissidents, Peter Lawler, and Us. (3rd July 2022) - Seaton, Paul
Abstract: During the Cold War, Peter Augustine Lawler was a close student of the great anti-Communist dissidents, Aleksandr Solzhenitsyn and Váçlav Havel. They taught him not only about the nature of Soviet Communism, but about modernity tout court . From both, he learned a positive lesson as well, the reality of the human person. Falsified by modern thought and directly assaulted by communist ideocracy, the truth of the person was the chief positive lesson of the Cold War, and one that Peter applied to the postwar situation as well. In our day, there are comparable reasons for cultivating "a personal point of view."